1996
DOI: 10.5962/bhl.title.47142
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome assignment of human genes / by Ann M. Kays

Abstract: Two human genes were assigned to chromosomes. Cartilage-derived morphogenic protein 1 (CDMPl-PEN) was assigned to chromosome 20 and asialoglycoprotein receptor 2 (ASGR2) was assigned to one of six different chromosomes using the polymerase chain reaction (PCR) and gel electrophoresis (Chang, Spiess). PCR is a DNA amplification technique in which a specific sequence is exponentially amplified through the action of a thermostable enzyme that polymerizes complementary nucleotides to a single stranded DNA template… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The Figures 4(b) and 5(a) shown new results investigated in present study, which is observed a distortion of the temperatures field and as consequence a variation of the Nusselt number caused mainly by the distribution of the non-uniform wall temperature (Case I and II, with fluid air and Re=65000, respectively). Most applications can be approximated by the functions sine and cosine in the wall, but we are able to resolve by means of the methodology presented, any peripheral heat flux variation that can be expressed by a Fourier expansion (Kays and Crawford [30]). The Figure 5(b) shows the comparisons of the behavior of the curves "Tb" and "DTb/dz" in the direction of the main flow for Case II and Case uniform wall temperature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Figures 4(b) and 5(a) shown new results investigated in present study, which is observed a distortion of the temperatures field and as consequence a variation of the Nusselt number caused mainly by the distribution of the non-uniform wall temperature (Case I and II, with fluid air and Re=65000, respectively). Most applications can be approximated by the functions sine and cosine in the wall, but we are able to resolve by means of the methodology presented, any peripheral heat flux variation that can be expressed by a Fourier expansion (Kays and Crawford [30]). The Figure 5(b) shows the comparisons of the behavior of the curves "Tb" and "DTb/dz" in the direction of the main flow for Case II and Case uniform wall temperature.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to develop a formula similar to Kays and Crawford [30], and a new expression for the turbulent energy equation can be presented as:…”
Section: ( )mentioning
confidence: 99%
See 2 more Smart Citations
“…The turbulent thermal conductivity within the boundary layer can be written as [13] where ß^ is the ratio of the turbulent viscosity to the molecular viscosity (4) Another formula was proposed by Kays and others [19] and cited by Kays [18] as the following expression:…”
Section: Turbulent Thermal Conductivity Modelmentioning
confidence: 99%